Improved effect and mechanism of propofol on vascular hyporeactivity in septic rats - SUN Yue; ZHANG Jie; ZHANG Bindan (陆军军医大学学报, 2024)
Objective To observe the improved effect of propofol on vascular hyporeactivity in septic rats and its underlying mechanism. Methods A total of 96 SD rats (12 weeks old, both genders, weighing 200~220 g) were randomly divided into sham group (n=16), sepsis group (n=16, cecal ligation and puncture), propofol group (n=16), propofol+ROCK inhibitor Y-27632 group (n=16), propofol+PKCα inhibitor GO6976 group (n=16), propofol+IP3 inhibitor 2-APB group (n=8) and propofol+gap junction inhibitor metoclopramide sodium (Movens) group (n=8). In vitro vascular ring reactivity and vascular calcium sensitivity were measured to observe the improved effects of propofol on vascular hyporeactivity in septic rats and its relationships with RhoA/ROCK, PKCα, IP3 and cell gap junction. Results Determination of in vitro vascular ring and calcium sensitivity showed that the contractile reactivity to norepinephrine (NE) and to calcium sensitivity were significantly decreased in the arterial rings isolated from the septic rats compared with those from the sham group, with the dose-response curve shifting to the right, and most significant decrease by 51.42% in the superior mesenteric artery (SMA, P < 0.05). Propofol treatment significantly improved the hyporeactivity and calcium sensitivity of the vessels isolated from the septic rats, especially those of the femoral artery with a recovery rate of 89.57% (P < 0.05). In comparison with the propofol group, the dose-response curves of the propofol+Y-27632 group and the propofol+GO6976 group were shifting to right, indicating that Y-27632 and GO6976 could significantly inhibit the amelioration of propofol on calcium sensitivity of SMA in severely septic rats with an inhibitory rate of 146.95% and 88.63% (P < 0.05), respectively. Isolated vascular reactivity measurement demonstrated that Y-27632 and Movens treatment significantly antagonized the ameliorated role of propofol on hyporeactivity of blood vessels from the septic rats with an inhibitory rate of 40.79% and 169.90% (P < 0.05), separately, while no such effect was observed in the propofol+GO6976 and propofol+2-APB groups. Conclusion Propofol treatment can significantly improve vascular hyporeactivity of septic rats, which may attribute to the increase of vascular calcium sensitivity through RhoA/ROCK pathway.